A systematic literature review on the ontology of media convergence - Tang, Jin Long; Li, Yi; Chang, Peng Kee; Nur Haniz Mohd Nor,; Kho, Suet Nie (Penerbit Universiti Kebangsaan Malaysia, 2024)
Media convergence is a process in which the media adapts to the audience's digital media usage habits. It is a response to the rapid development of technologies and is affected by multiple factors. A systematic literature review of media convergence is crucial for comprehensively understanding the complex merging of traditional and digital media, identifying research gaps, and evaluating trends that inform both theoretical developments and practical applications. This approach also enhances academic rigor, guiding future research and informing policy decisions in a rapidly evolving media landscape. This study employs a systematic literature review methodology, adhering to the PRISMA 2020 standards for classification and summarization. It comprehensively analyzes over 5,000 academic articles on media convergence sourced from three main databases, namely WoS, Scopus and CSSCI, ultimately selecting 53 articles that meet the inclusion criteria. The findings indicated four main components worthy of future studies of media convergence, namely cultural, content, technology, and economic convergence. Each of these components are discussed to reflect the current trend of media convergence worldwide. These four components should be integrated into theoretical framework of media convergence to refine the rapid changes to the interaction between media and technologies worldwide.From this SLR, future studies on media convergence might explore audience behavior, economic models, content diversity, regulatory challenges, and technological innovations, building on insights from the systematic literature review.